Outcome of Candida Parapsilosis Complex Infections Treated with Caspofungin in Children - Devrim, İlker (Mediterr J Hematol Infect Dis, 2016)
BACKGROUND: We aimed to evaluate the correlation of caspofungin E-tests with the prognosis and response to caspofungin therapy of Candida parapsilosis complex bloodstream infections in children hospitalized in a pediatric intensive care unit. METHODS: All children who had C. parapsilosis complex bloodstream infections and who were treated with caspofungin were included in this retrospective study. For each patient, the following parameters, including all consecutive blood and central venous catheter (CVC) cultures, the duration between diagnosis and CVC removal, mortality rate, relapses of the C. parapsilosis complex infections as well as the demographic features, were recorded. RESULTS: The central venous catheter survival rate was 33.3% under caspofungin treatment. In 92.4 % of the patients, the negative culture was achieved within a median duration of 12.5 days. The rate of relapses was 18.9%. The overall mortality rate was 37.7% (20 of 53 patients), and the 30-days mortality rate was 7.5% (4 of 53 patients). There was no statistically significant difference between the groups with MIC<2 mg/l and MIC =2 mg/l using CVC survival rate; rate and duration of achieving negative blood culture for C. parapsilosis complex; duration of hospital stay; rate and duration of relapses; overall mortality and 30-days mortality. CONCLUSIONS: The beneficial effects of Caspofungin on biofilms has been shown in vivo, while its impact in children for maintenance of CVC was limited in our study but should not be underestimated in children who strongly need the presence of CVCs. The clinicians should weigh their priority for their patients and choose the optimal antifungal therapy for C. parapsilosis complex infections in children.